Nas trilhas da co-educação e do ensino misto em Sergipe (1842 - 1889) - Andrade, Élia Barbosa de (2008)
The present study has as goal to build a history of the co-education and of the mixed teaching in Sergipe, where neferrend her form pedagogie softeu some restrictions.The part of the societ.The temporary mark of the work is going fron 1842 to 1889.Starting from the sources,we tried to show the polemics That caused the implatação of the co-education and of the mixed schools in the.country,and the representations that the societ of the lime had in relation to such pratices.For we wderstand the whole problem that involved the implatação in the referred pedagogie way,he/she made hinself necessary a brief one to look at about the public instruction in the period of the empire.Besides verifying as the cathlie church it was positioned in relation to the boys mixture and girls in the sane school space,we threw,also,the glance about the reprsentation that was had of the masculine and of the feminine in the public instruction starting from the callicted data we reconstructed some ftagmentas of the history of the history of the education in the county, ftagmentas those that facilitated us to inderstand the educational context that sponsonred the implatação of the co-education and of the mixed teaching in the school space of the country sergipana.